Mechanical performance of ETC RC beam with U-framed AFRP laminates under a static load condition - Loganathan, P.; Mohanraj, R.; Senthilkumar, S.; Yuvaraj, K. (Revista de la Construcción. Journal of Construction, 2022)
In the presented paper, an attempt has been made to first find the permeability of the Euphorbia tortilis cactus (ETC) concrete by the water permeability method and infiltration method. After that, the flexural strength of the ETC RC beam wrapped with AFRP kelvar 149 is carried out by a 2-point load test. This research aimed to develop a more durable, flexural, and sustainable beam under static load. Based on the state-of-the-art information available in the literature, 3-layer Kelvar 149 AFRP is considered as a laminate to solve the deflections of the ETC beam. In this project, RCC beams were strengthened by ETC and aramid FRP sheets. Novel results are obtained by different layers and patterns of Aramid FRP sheets. Based on the investigation 3-layers Kelvar 149 perform well than a normal concrete beam. As no result based on hydraulic conductivity and drying shrinkage of a beam with AFRP laminates are available in the literature, the obtained results are validated with the finite element method (ABAQUS) under static load conditions.